Secondary battery and electronic device
By adjusting the porosity and thickness in the positive and negative electrode material layers of lithium-ion batteries, the problem of insufficient wettability of the electrolyte is solved, the charge transfer rate of lithium ions is improved, and the higher magnification and low-temperature capacity retention rate is achieved, and the improvement of the improvement of the The power performance of the battery.
Patent Information
- Application Number
- CN202310783930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium-ion batteries have poor electrolyte infiltrates inside the electrode sheet, resulting in a decrease in the liquid phase transmission rate and solid phase diffusion rate of lithium ions, and it is impossible to effectively improve the magnification capacity retention rate and low-temperature capacity retention rate.
By adjusting the porosity and thickness in the positive electrode and negative electrode material layers, ensuring the wettability of the electrolyte, thereby improving the charge transfer and migration rate of lithium ions, the specific positive electrode and negative electrode material layer design, including the porosity of the positive electrode material layer. 40%-50%, the porosity of the negative electrode material layer is between 40%-50%, and a high-pressure density material layer is formed by rolling.
The power performance of lithium-ion batteries is significantly improved and the power performance of the battery is improved.
Smart Images

Figure CN119230708A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a secondary battery and an electronic device. Background Art
[0002] With the continuous development of secondary batteries, in order to obtain secondary batteries with better electrical performance, the industry's requirements for the power performance of secondary batteries are constantly increasing. Improving the power performance of secondary batteries mainly includes two aspects: rate capacity retention rate and low temperature capacity retention rate.
[0003] Existing secondary batteries (such as lithium-ion batteries) generally have the problem of poor electrolyte infiltration inside the electrode, which leads to a decrease in the liquid phase transmission rate of lithium ions, and also a decrease in the solid phase diffusion rate of lithium ions; it is impossible to keep both the rate capacity retention rate and the low temperature capacity retention rate at a better level. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a secondary battery and an electronic device in order to overcome the defect of poor power performance of existing secondary batteries. The secondary battery of the present invention has a high rate capacity retention rate and low temperature capacity retention rate, and improves its power performance.
[0005] In this field, in order to make the secondary battery have a high energy density, the positive and negative electrodes are generally designed with thick coating and high compaction density. However, such a design will result in poor electrolyte wetting inside the positive and negative electrodes, a reduced liquid phase transmission rate of lithium ions, and a reduced solid phase diffusion rate of lithium ions. If the coating amount is simply reduced, the energy density of the secondary battery will be reduced. Therefore, how to make the secondary battery have a high energy density while improving its capacity retention rate, thereby improving its power performance, has always been a difficult problem to be solved by those skilled in the art.
[0006] The present invention mainly solves the above technical problems through the following technical solutions.
[0007] In a first aspect, the present invention provides a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector; characterized in that the positive electrode material layer and the negative electrode material layer satisfy:
[0008] p 1 The value range is 40%-50%, p 2 The value range is 40%-50%, p 1 :p 2 is (0.8-1):1;
[0009] t 1 The value range is 15-70μm, t 2 The value range is 15-70μm, t 1 :t 2 is (1.3-2):1;
[0010] Among them, p 1 is the porosity of the positive electrode material layer, p 2 is the porosity of the negative electrode material layer, t 1 is the single-sided thickness of the positive electrode material layer, t 2 is the single-sided thickness of the negative electrode material layer.
[0011] In a second aspect, the present invention provides an electronic device comprising the secondary battery as described above.
[0012] The positive and progressive effects of the present invention are:
[0013] The secondary battery of the present invention improves the rate capacity retention rate and low temperature capacity retention rate of the secondary battery by ensuring the wettability of the electrolyte and improving the charge transfer and migration rate of lithium ions. The power performance of the secondary battery is better. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a comparison chart of the capacity retention rate under different discharge rate conditions of Examples 1-3;
[0015] Figure 2 It is a comparison chart of the capacity retention rate under different temperature conditions of Examples 1-3. DETAILED DESCRIPTION
[0016] Secondary battery
[0017] In a first aspect, the present invention provides a secondary battery, which includes a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, and the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector; the positive electrode material layer and the negative electrode material layer satisfy:
[0018] p 1 The value range is 40%-50%, p 2 The value range is 40%-50%, p 1 :p 2 is (0.8-1):1;
[0019] t 1 The value range is 15-70μm, t 2 The value range is 15-70μm, t1 :t 2 is (1.3-2):1;
[0020] Among them, p 1 is the porosity of the positive electrode material layer, p 2 is the porosity of the negative electrode material layer, t 1 is the single-sided thickness of the positive electrode material layer, t 2 is the single-sided thickness of the negative electrode material layer.
[0021] Those skilled in the art should know that the positive electrode material layer may include a positive electrode active material, a positive electrode conductor and a positive electrode binder; the negative electrode material layer may include a negative electrode active material, a negative electrode conductor and a negative electrode binder.
[0022] In some embodiments, the positive electrode current collector generally comprises aluminum foil.
[0023] In some embodiments, the negative electrode current collector generally comprises copper foil.
[0024] In a preferred embodiment, the porosity p of the positive electrode material layer is 1 The value range is 41%-46%.
[0025] In a preferred embodiment, the porosity p of the negative electrode material layer is 2 The value range is 45%-50%.
[0026] In a specific embodiment, p 1 is 45%, p 2 is 49%.
[0027] In a specific embodiment, p 1 is 43%, p 2 It is 47%.
[0028] In a specific embodiment, p 1 is 41%, p 2 is 45%.
[0029] In a specific embodiment, p 1 is 42%, p 2 It is 46%.
[0030] In a specific embodiment, p 1 is 44%, p 2 It is 48%.
[0031] In a specific embodiment, p 1 is 46%, p 2 is 50%.
[0032] In the present invention, the porosity of the positive electrode material layer and the negative electrode material layer can be controlled by adjusting the compaction density of the positive and negative electrode material layers.
[0033] In a preferred embodiment, the compaction density of the positive electrode material layer is 1.6-2.7 g / cm 3 .
[0034] In a preferred embodiment, the compaction density of the negative electrode material layer is 1.0-1.7 g / cm 3 .
[0035] In a preferred embodiment, the single-sided thickness of the positive electrode material layer is 1 The value range is 20-70μm.
[0036] In a preferred embodiment, the single-sided thickness of the negative electrode material layer is 2 The value range is 15-40μm.
[0037] In a specific embodiment, t 1 38.5 μm, t 2 is 22μm.
[0038] In a specific embodiment, t 1 53.5μm, t 2 It is 31μm.
[0039] In a specific embodiment, t 1 69μm, t 2 It is 39.5μm.
[0040] In a specific embodiment, t 1 60μm, t 2 is 32μm.
[0041] In a specific embodiment, t 1 54μm, t 2 It is 29μm.
[0042] In a specific embodiment, t 1 48μm, t 2 is 26μm.
[0043] In a preferred embodiment, the single-sided surface density b of the positive electrode sheet is 1 45-120g / m 2 The single-sided surface density of the positive electrode sheet refers to the mass of the positive electrode material layer per square meter on one side of the positive electrode sheet.
[0044] In a preferred embodiment, the single-sided surface density b of the negative electrode sheet is 2 18-50g / m2 The single-sided surface density of the negative electrode plate refers to the mass of the negative electrode material layer per square meter on one side of the negative electrode plate.
[0045] In a specific embodiment, b 1 50g / m 2 , b 2 19g / m 2 .
[0046] In a specific embodiment, b 1 70g / m 2 , b 2 26g / m 2 .
[0047] In a specific embodiment, b 1 90g / m 2 , b 2 34g / m 2 .
[0048] Those skilled in the art should know that the preparation method of the positive electrode sheet includes: coating the positive electrode slurry on the positive electrode collector, and sequentially drying and rolling to form the positive electrode material layer; wherein the positive electrode slurry includes a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and a solvent.
[0049] In a preferred embodiment, the single-side effective coating amount a of the positive electrode current collector is 1 45-120g / m 2 .
[0050] In a preferred embodiment, in the method for preparing the positive electrode sheet, the rolling pressure is 20-120t.
[0051] Those skilled in the art should know that the method for preparing the negative electrode sheet includes: coating the negative electrode slurry on the positive electrode collector, and sequentially drying and rolling to form the negative electrode material layer; wherein the negative electrode slurry includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a solvent.
[0052] In a preferred embodiment, the single-side effective coating amount a of the negative electrode current collector is 2 18-50g / m 2 .
[0053] In a preferred embodiment, in the method for preparing the negative electrode sheet, the rolling pressure is 20-80t.
[0054] In the present invention, the single side refers to one side of the positive electrode current collector or the negative electrode current collector; the effective coating amount refers to the coating amount of the components other than the solvent in the positive electrode slurry or the negative electrode slurry on the current collector.
[0055] In a specific embodiment, a 1 50g / m 2 , a 2 19g / m 2 .
[0056] In a specific embodiment, a 1 70g / m 2 , a 2 26g / m 2 .
[0057] In a specific embodiment, a 1 90g / m 2 , a 2 34g / m 2 .
[0058] In the present invention, the positive electrode sheet and the negative electrode sheet are respectively formed by rolling to achieve the positive and negative electrode material layers with the above compaction density.
[0059] In the present invention, the positive electrode plate generally includes a positive electrode current collector and a positive electrode material layer formed on the positive electrode current collector, the positive electrode material layer includes a positive electrode active substance and optional conductive agent and binder, and the added amount can be adjusted within 1-50% of the total amount of the positive electrode material layer according to different needs; the negative electrode plate generally includes a negative electrode current collector and a negative electrode material layer formed on the negative electrode current collector, the negative electrode material layer includes a negative electrode active substance and optional binder and conductive agent, and the added amount can be adjusted within 1-50% of the total amount of the negative electrode material layer according to different needs.
[0060] There is no special selection for the positive electrode active material, the negative electrode active material, the conductive agent, the binder, the positive electrode current collector and the negative electrode current collector, and they are all conventional materials in the art.
[0061] The positive electrode active material may be a material commonly used in the art, including but not limited to one or more of lithium iron phosphate material, lithium iron manganese phosphate material, nickel-cobalt-manganese ternary material and lithium-rich manganese-based material.
[0062] Among them, the negative electrode active material is a material that can embed and de-embed lithium. It includes but is not limited to carbon materials such as crystalline carbon (natural graphite and artificial graphite, etc.), amorphous carbon, carbon-coated graphite and resin-coated graphite, or oxide materials such as indium oxide, silicon oxide, tin oxide, lithium titanate, zinc oxide, lithium oxide, etc. It can also be lithium metal or a metal material that can form an alloy with lithium, wherein the metal material that can form an alloy with lithium is, for example, Cu, Sn, Si, Co, Mn, Fe, Sb and Ag; binary or ternary alloys containing these metals and lithium can also be used as negative electrode active materials. These negative electrode active materials can be used alone or in combination of two or more. From the perspective of high energy density, carbon materials such as graphite can also be used in combination with Si, Si alloys, Si oxides and other Si-based materials.
[0063] The conductive agent is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.
[0064] The binder is a component that helps the active material to bind to the conductive agent and helps the active material to bind to the current collector. It can usually be selected from polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers.
[0065] Among them, the positive electrode current collector is a substrate supporting the electrode active material, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The positive electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0066] In the present invention, the secondary battery is preferably a lithium ion battery.
[0067] In the present invention, those skilled in the art know that the secondary battery generally further includes a separator and an electrolyte.
[0068] Isolation film
[0069] The separator provided between the positive electrode and the negative electrode uses an insulating film with high ion permeability and high mechanical strength. The separator is typically 9-18 μm thick; 5-300 μm pore size; 180-380 s / 100 mL air permeability; and 30% to 50% porosity. As a separator, a sheet or non-woven fabric made of the following substances is used: an olefin polymer such as polypropylene; glass fiber or polyethylene, which has chemical resistance and hydrophobicity.
[0070] Electrolyte
[0071] The electrolyte used in the secondary battery as described above generally includes a non-aqueous solvent, a lithium salt, and an additive.
[0072] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0073] Among them, LiPF 6 , LiBF 4 、LiN(SO 2 F) 2 (abbreviated as LiFSI), LiClO 4 、LiAsF 6 、LiB(C 2 O 4 ) 2 (abbreviated as LiBOB), LiBF 2 (C 2 O 4 ) (abbreviated as LiDFOB), LiN(SO 2 RF) 2 、LiN(SO 2 F)(SO 2 Preferably, the content of the electrolyte is 5-20%.
[0074] The additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), dithiothreitol sulfate, 1,3-propane sultone (PS), propene sultone and 1,4-butane sultone. The conventional amount of the additive in the electrolyte is 1-4% of the electrolyte, for example 2%.
[0075] In the present invention, the secondary battery is generally any one of a square-shell battery, a soft-pack battery or a cylindrical battery, and the square-shell battery is taken as an example for description.
[0076] The secondary battery can be prepared by conventional methods in the art. Generally, the preparation method of the secondary battery includes the following steps: the positive electrode sheet, the negative electrode sheet and the separator are sequentially cut, cut and stacked or wound to form a bare cell, and then the bare cell is loaded into a shell, and the water content is fully baked to be below 450ppm, and the processes of liquid injection, formation, sealing, inspection and the like are completed to prepare a square shell battery.
[0077] Electronic Devices
[0078] A second aspect of the present invention provides an electronic device comprising the secondary battery described above.
[0079] Exemplarily, the electronic device described in the present invention may be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, a video recorder, a portable printer / copier, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system and a backup power supply, etc.
[0080] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0081] The lithium ion batteries of Examples 1-6 and Comparative Examples 1-5 are prepared by the following method:
[0082] (1) Preparation of positive electrode sheet
[0083] Lithium iron phosphate is used as the positive electrode active material, and the positive electrode active material is mixed with polyvinylidene fluoride as a binder and small particles of conductive carbon black (hereinafter referred to as Super P) as a conductive agent at a weight ratio of 95:2.5:2.5, and N-methylpyrrolidone (NMP) is added. The system is stirred under the action of a vacuum mixer until it becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on a 15μm aluminum foil current collector; the aluminum foil is dried at room temperature and transferred to a 120°C blast oven for drying for 1h, and then cold pressed, cut, and finally rolled to obtain a positive electrode sheet. The rolling pressure is 20-120t, and the compaction density of the obtained positive electrode material layer is 1.6-2.7g / cm 3 .
[0084] (2) Preparation of negative electrode sheet:
[0085] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder. They are mixed in a mass ratio of 96:2:1:1 and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the 8μm negative electrode current collector copper foil; the copper foil is dried at room temperature and transferred to a 120℃ blast oven for drying for 1h, and then cold pressed and cut to obtain the negative electrode sheet. The rolling pressure is 20-80t, and the compaction density of the negative electrode material layer is 1.0-1.7g / cm 3 .
[0086] (3) Preparation of electrolyte:
[0087] In an argon atmosphere glove box with a water content of <10ppm, battery-grade (referring to the purity level that meets the battery performance requirements) ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC) and ethyl acetate (EA) are mixed in a mass ratio of 1:1:2:6 to form an organic solvent.
[0088] (4) Lithium-ion battery preparation:
[0089] A 12 μm thick polypropylene film (PP) was used as a separator. The positive electrode sheet, separator, and negative electrode sheet prepared above were stacked in sequence, so that the separator was placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. Then, the aluminum plastic film was wrapped outside, transferred to a vacuum oven at 120°C for drying, and the above-prepared electrolyte 3.0 g / Ah was injected and sealed, and the electrolyte was formed, and finally a soft pack battery (i.e., lithium-ion battery) with a capacity of 1 Ah was prepared.
[0090] In addition to the above-mentioned preparation methods, different parameter conditions involved in the preparation process of the lithium ion batteries of Examples 1-6 and Comparative Examples 1-5 are selected as follows:
[0091] Example 1
[0092] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 50 g / m 2 The single-sided thickness of the formed positive electrode material layer is 38.5 μm, and the porosity is 45%; the thickness of the positive electrode sheet is 92 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0093] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 19 g / m 2 The single-sided thickness of the formed negative electrode material layer is 22 μm, and the porosity is 49%; the thickness of the negative electrode sheet is 52 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0094] Example 2
[0095] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 70 g / m 2 The single-sided thickness of the formed positive electrode material layer is 53.5 μm, and the porosity is 43%; the thickness of the positive electrode sheet is 122 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0096] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 26 g / m 2 The single-sided thickness of the formed negative electrode material layer is 31 μm, and the porosity is 47%; the thickness of the negative electrode sheet is 70 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0097] Example 3
[0098] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 90 g / m 2 The single-sided thickness of the formed positive electrode material layer is 69 μm, and the porosity is 41%; the thickness of the positive electrode sheet is 153 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0099] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 34 g / m 2 The single-sided thickness of the formed negative electrode material layer is 39.5 μm, and the porosity is 45%; the thickness of the negative electrode sheet is 87 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0100] Example 4
[0101] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 80 g / m 2 The single-sided thickness of the formed positive electrode material layer is 60 μm, and the porosity is 42%; the thickness of the positive electrode sheet is 135 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0102] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 30 g / m 2 The single-sided thickness of the formed negative electrode material layer is 32 μm, and the porosity is 46%; the thickness of the negative electrode sheet is 72 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0103] Example 5
[0104] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 60 g / m 2 The single-sided thickness of the formed positive electrode material layer is 54 μm, and the porosity is 44%; the thickness of the positive electrode sheet is 123 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0105] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 23 g / m 2 The single-sided thickness of the formed negative electrode material layer is 29 μm, and the porosity is 48%; the thickness of the negative electrode sheet is 66 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0106] Example 6
[0107] The single-surface density of the positive electrode material layer on the positive electrode sheet of this embodiment is 61 g / m 2 The single-sided thickness of the formed positive electrode material layer is 48 μm, and the porosity is 46%; the thickness of the positive electrode sheet is 111 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0108] The single-surface density of the negative electrode material layer on the positive electrode sheet of this embodiment is 22 g / m 2 The single-sided thickness of the formed negative electrode material layer is 26 μm, and the porosity is 50%; the thickness of the negative electrode sheet is 60 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0109] Comparative Example 1
[0110] The single-sided surface density of the positive electrode material layer on the positive electrode sheet of this comparative example is 80 g / m 2 The single-sided thickness of the formed positive electrode material layer is 60 μm, and the porosity is 34%; the thickness of the positive electrode sheet is 135 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0111] The single-sided surface density of the negative electrode material layer on the positive electrode sheet of this comparative example is 30 g / m 2 The single-sided thickness of the formed negative electrode material layer is 32 μm, and the porosity is 38%; the thickness of the negative electrode sheet is 72 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0112] Comparative Example 2
[0113] The single-sided surface density of the positive electrode material layer on the positive electrode sheet of this comparative example is 107 g / m 2 The single-sided thickness of the formed positive electrode material layer is 80 μm, and the porosity is 42%; the thickness of the positive electrode sheet is 175 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0114] The single-sided surface density of the negative electrode material layer on the positive electrode sheet of this comparative example is 39g / m 2 The single-sided thickness of the formed negative electrode material layer is 42 μm, and the porosity is 46%; the thickness of the negative electrode sheet is 92 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0115] Comparative Example 3
[0116] The single-sided surface density of the positive electrode material layer on the positive electrode sheet of this comparative example is 106 g / m 2 The single-sided thickness of the formed positive electrode material layer is 80 μm, and the porosity is 42%; the thickness of the positive electrode sheet is 175 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0117] The single-sided surface density of the negative electrode material layer on the positive electrode sheet of this comparative example is 30 g / m 2 The single-sided thickness of the formed negative electrode material layer is 32 μm, and the porosity is 56%; the thickness of the negative electrode sheet is 72 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0118] Comparative Example 4
[0119] The single-sided surface density of the positive electrode material layer on the positive electrode sheet of this comparative example is 50 g / m 2 The single-sided thickness of the formed positive electrode material layer is 38.5 μm, and the porosity is 49%; the thickness of the positive electrode sheet is 92 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0120] The single-sided surface density of the negative electrode material layer on the positive electrode sheet of this comparative example is 19 g / m 2 The single-sided thickness of the formed negative electrode material layer is 22 μm, and the porosity is 45%; the thickness of the negative electrode sheet is 52 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0121] Comparative Example 5
[0122] The single-sided surface density of the positive electrode material layer on the positive electrode sheet of this comparative example is 50 g / m 2 The single-sided thickness of the formed positive electrode material layer is 38.5 μm, and the porosity is 45%; the thickness of the positive electrode sheet is 92 μm, which is the sum of the thickness of the positive electrode material layer and the positive electrode current collector.
[0123] The single-sided surface density of the negative electrode material layer on the positive electrode sheet of this comparative example is 19 g / m 2 The single-sided thickness of the formed negative electrode material layer is 22 μm, and the porosity is 60%; the thickness of the negative electrode sheet is 52 μm, which is the sum of the thickness of the negative electrode material layer and the negative electrode current collector.
[0124] Effect Example 1
[0125] 1. Test of rate capacity retention and temperature capacity retention
[0126] The capacity retention rates of Examples 1-6 under different conditions were tested using a Newwell CTE-8008-5V200A device.
[0127] Figure 1 The capacity retention rates of Examples 1-3 under different discharge rate conditions correspond to the data in Table 1. The capacity retention rates of Examples 1-6 and Comparative Examples 1-5 under discharge rate conditions of 1C, 5C, 10C and 15C are shown in Table 1.
[0128] Table 1
[0129]
[0130] As can be seen from Table 1, under different discharge rate conditions of 1C, 5C, 10C and 15C, the capacity retention rate of the lithium ion batteries prepared in Examples 1-6 under different discharge rate conditions is 60% or more. Among them, when the discharge rate is 1C / 5C, the capacity retention rate of the lithium ion batteries prepared in Examples 1-6 can be maintained at 85% or more; when the discharge rate is 1C / 10C, the capacity retention rate of the lithium ion batteries prepared in Examples 1-6 can still be maintained at 75% or more; when the discharge rate is 1C / 15C, the capacity retention rate of the lithium ion batteries prepared in Examples 1-6 can still be maintained at 60% or more.
[0131] However, when the discharge rate of comparative example 5 is 1C / 5C, its capacity retention rate has been reduced to 84%; when the discharge rates of comparative examples 1-3 are 5C and 10C, their capacity retention rates cannot reach 85% and 75%.
[0132] Figure 2 The capacity retention rates of Examples 1-3 under different temperature conditions correspond to the data in Table 1. The capacity retention rates of Examples 1-6 and Comparative Examples 1-5 under the temperature conditions of -25°C, 0°C and 25°C are shown in Table 1.
[0133] As can be seen from Table 1, under different temperature conditions of -25°C, 0°C and 25°C, the capacity retention rates of the lithium ion batteries of Examples 1-6 and Comparative Examples 1-5 are all 65% or above. Among them, at a temperature of 0°C, the capacity retention rates of the lithium ion batteries prepared in Examples 1-6 can all be maintained at 80%; and at a temperature of -25°C, the capacity retention rates of the lithium ion batteries prepared in Examples 1-8 can still be maintained at more than 65%.
[0134] The capacity retention rates of the lithium-ion batteries prepared in Comparative Examples 1-5 cannot reach 65%.
[0135] 2. Low temperature DC impedance test
[0136] Under the conditions of -20°C, 3C, discharge for 10s, and 50% remaining capacity (SOC), the direct current resistance (DCR) of Examples 4-6 and Comparative Examples 1-3 was tested.
[0137] Table 2 shows the test results of the DC resistance ratio of Examples 4-6 and Comparative Examples 1-3. Taking the DC resistance ratio of Example 4 as 100%, the DC resistance ratios of Examples 5-6 and Comparative Examples 1-3 are shown in the following table.
[0138] Table 2
[0139] DC resistance DCR ratio Example 4 100% Example 5 90% Example 6 80% Comparative Example 1 110% Comparative Example 2 113% Comparative Example 3 120%
[0140] As can be seen from Table 2, the DC impedance ratios of Examples 4-6 are all less than 100%. However, due to the small porosity and / or large thickness of the positive and negative electrode material layers, the electrolyte infiltration is affected, and the charge transfer and migration rate of lithium ions are reduced, and the DC impedance ratios of Comparative Examples 1-3 will exceed 100%.
Claims
1. A secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one side of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector; characterized in that: The positive electrode material layer and the negative electrode material layer satisfy: The value range of p1 is 40%-50%, the value range of p2 is 40%-50%, and p1:p2 is (0.8-1):1; The value range of t1 is 15-70 μm, the value range of t2 is 15-70 μm, and t1:t2 is (1.3-2):1; Wherein, p1 is the porosity of the positive electrode material layer, p2 is the porosity of the negative electrode material layer, t1 is the single-sided thickness of the positive electrode material layer, and t2 is the single-sided thickness of the negative electrode material layer.
2. The secondary battery according to claim 1, wherein: The value range of p1 is 41%-46%.
3. The secondary battery according to claim 1, wherein: The value range of p2 is 45%-50%.
4. The secondary battery according to claim 1, wherein: The value range of t1 is 20-70 μm.
5. The secondary battery according to claim 1, wherein: The value range of t2 is 15-40 μm.
6. The secondary battery according to claim 1, wherein: The single-sided surface density b1 of the positive electrode sheet is 45-120 g / m 2 .
7. The secondary battery according to claim 1, wherein: The single surface density b2 of the negative electrode plate is 18-50 g / m 2 .
8. The secondary battery according to claim 1, wherein: The preparation method of the positive electrode sheet comprises: coating the positive electrode slurry on the positive electrode current collector, drying and rolling in sequence to form the positive electrode material layer; the single-side effective coating amount a1 of the positive electrode current collector is 45-120 g / m 2 .
9. The secondary battery according to claim 1, wherein: The preparation method of the negative electrode sheet comprises: coating the negative electrode slurry on the positive electrode current collector, drying and rolling in sequence to form the negative electrode material layer; the single-side effective coating amount a2 of the negative electrode current collector is 18-50g / m 2 .
10. An electronic device, characterized in that: It comprises the secondary battery as claimed in any one of claims 1 to 9.
